2021
DOI: 10.3390/v13061053
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Autophagy in Varicella Zoster Virus Infection

Abstract: Autophagy is an evolutionary conserved cellular process serving to degrade cytosolic organelles or foreign material to maintain cellular homeostasis. Autophagy has also emerged as an important process involved in complex interactions with viral pathogens during infection. It has become apparent that autophagy may have either proviral or antiviral roles, depending on the cellular context and the specific virus. While evidence supports an antiviral role of autophagy during certain herpesvirus infections, numerou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Despite a report of mitochondrial abnormalities, no studies to date have evaluated the role of mitophagy in VZV infection. Moreover, all available data on the role of autophagy in VZV has been acquired using non-ocular models (116). For an in depth review on what is known on the relationship between autophagy and VZV infection, the reader is directed to the review by Heinz et al (116).…”
Section: Viral Keratitismentioning
confidence: 99%
“…Despite a report of mitochondrial abnormalities, no studies to date have evaluated the role of mitophagy in VZV infection. Moreover, all available data on the role of autophagy in VZV has been acquired using non-ocular models (116). For an in depth review on what is known on the relationship between autophagy and VZV infection, the reader is directed to the review by Heinz et al (116).…”
Section: Viral Keratitismentioning
confidence: 99%
“…Concerning HSV-1, many studies revealed its escape strategies and the potential protective effects of autophagy during infection [ 132 , 133 ]. However, VZV lacks these specific genes encoding proteins interfering with autophagy, suggesting that in some cases, VZV may be able to exploit autophagy for its replication [ 134 , 135 ].…”
Section: Regulation Of Apoptosis Autophagy Er Stress and Stress Granu...mentioning
confidence: 99%
“…Autophagy is a highly conserved cytoplasmic pathway of maintaining physiological stability in eukaryotes, which sequesters and removes unwanted self-materials by degrading them into amino acids for re-use. A growing number of studies established an antiviral role of autophagy in the host response against pathogenic infection [ 103 , 104 ]. It was reported that the interaction of IBDV VP2 with heat shock protein 90 (HSP90AA1) induced autophagy through the HSP90AA1-AKT-mTOR pathway early during infection, and the activated autophagy inhibited virus replication ( Figure 1 ), suggesting that autophagy is involved in host defense against IBDV infection [ 105 ].…”
Section: Host Response To Ibdv Infection At the Protein Levelmentioning
confidence: 99%